Isolation and Functional Analysis of a PISTILLATA-like MADS-Box Gene from Argan Tree (Argania spinosa) - Marwa Louati; Blanca Salazar-Sarasua; Edelín Roque; José Pío Beltrán; Amel Salhi Hannachi; Concepción Gómez-Mena (Plants, 2021)
Argan trees (Argania spinosa) belong to a species native to southwestern Morocco, playing an important role in the environment and local economy. Argan oil extracted from kernels has a unique composition and properties. Argan trees were introduced in Tunisia, where hundreds of trees can be found nowadays. In this study, we examined reproductive development in Argan trees from four sites in Tunisia and carried out the functional characterization of a floral homeotic gene in this non-model species. Despite the importance of reproductive development, nothing is known about the genetic network controlling flower development in Argania spinosa. Results obtained in several plant species established that floral organ development is mostly controlled by MADS-box genes and, in particular, APETALA3 (AP3) and PISTILLATA (PI) homologs are required for proper petal and stamen identity. Here, we describe the isolation and functional characterization of a MADS-box gene from Argania spinosa. Phylogenetic analyses showed strong homology with PI-like proteins, and the expression of the gene was found to be restricted to the second and third whorls. Functional homology with Arabidopsis PI was demonstrated by the ability of AsPI to confer petal and stamen identity when overexpressed in a pi-1 mutant background. The identification and characterization of this gene support the strong conservation of PI homologs among distant angiosperm plants.